Estimating and Integrating the Values of Tourism and Recreation Visitation to Parks and Protected Areas - Carlsen, Jack; Hughes, Michael (Mid-Sweden University, 2012)
The declaration of protected natural areas was historically based on preservation of unusual or distinctive natural phenomena, natural resource protection and opportunities for public recreation and tourism. Since the 1970s, the management focus of protected natural areas has shifted toward nature conservation or preservation in recognition of the ecological values and environmental services of the areas being protected. While now protected for ecological conservation, the continued and increasing popularity of these areas as places for recreation and tourism has generated significant social and economic value for the regions in which they are located. There are also universal values that have been recognised by UNESCO in nominating and declaring natural world heritage areas. Thus, there has emerged a range of ecological, socio-cultural, economic and universal values associated with parks and protected areas that have to be clearly understood by researchers, protected area managers and policy-makers to better inform optimal decision-making for policy, planning and management. This roundtable will be a discussion of the identification, quantification and integration of the full range of parks and protected natural area values around the world. It could include discussion of the typology of economic, social and environmental values and how these have been identified, measured and presented. There is also a need to integrate the full range of values into a data-base of protected areas. Understanding the full range of values and development of an integrated database will better inform optimal decision-making for protected natural area policy, planning and management.In developing a detailed understanding of the values of protected natural areas and agreed methods for assessing these values over time, the roundtable discussion will engender an approach that recognises the net benefits to society of monitoring and maintaining these places for present and future generations.